A case of descending necrotizing mediastinitis caused by odontogenic infection. Issue 4 (July 2020) - Egashira, Kazuhiro; Ohba, Seigo; Tsuchiya, Tomoshi; Narahara, Shun; Minamizato, Tokutaro; Takashi, I.; Asahina, Izumi
Abstract: Descending necrotizing mediastinitis (DNM) is a life-threatening pyogenic mediastinitis induced by caudal expansion of an odontogenic or laryngopharyngeal infection. We herein report a case of DNM that developed via the retrovisceral and pretracheal spaces in a patient on hemodialysis. A 52-year-old male was referred to our hospital because of pain in the bilateral mandibular molar regions, trismus, and bilateral swelling of the neck. The patient was undergoing hemodialysis for glomerulonephritis. The computed tomography images taken at the first visit revealed abscesses from the parapharyngeal to postpharyngeal spaces. Despite surgical drainage through the submandibular and submental approaches, the infection expanded caudally to the mediastinum and DNM developed. The infection disappeared after four surgical drainage procedures performed with cooperation between respiratory surgeons and internal medicine doctors. He underwent rehabilitation in another hospital. This case suggests the importance of collaboration with other departments early in the clinical course of DNM.